UTILISASI QUAY CONTAINER CRANE DAN PRODUKTIVITAS BONGKAR MUAT PETIKEMAS TERHADAP EFFECTIVE TIME KAPAL PETIKEMAS DI TERMINAL OPERASI 3 PT PELABUHAN TANJUNG PRIOK - Rini Setiawati; Mahendra Caehsa; Berlian Badarusman (Institut Transportasi dan Logistik Trisakti, 2017)
PT. Pelabuhan Indonesia II (IPC) was born as a follow up of Law No.21 of 1992 regarding port business entity. PT. Pelindo II is one of the state-owned enterprises in the transportation sector engaged in the management and exploitation of public ports. The research objective is to find out how big the influence of quay container crane utilization and productivity of loading and unloading to effectiveness of container vessel. Analysis method used in this research was multiple linear regression analysis, multiple correlation analysis, Pearson correlation analysis, determinant coefficient and hypothesis test (f-test)The result of analysis and discussion between quay container crane utilization and container cargo loading productivity with effective time of container vessel is shown by equation of double linear regression line, that is Y = 10.673 + 0.209X1 - 0.056X2. The value of double correlation R = 0.713, there is a strong and undirectional relationship between independent and dependent variables. Pearson correlation test is worth 0.712, Test coefficient determinant equal to 48% means contribution of X1 and X2 to Y 50.8%, while 49.2% is another factor. From the result of F-test show that F count> F table (4,640> 4,26), hence Ho = rejected and Ha = accepted, there is influence between quay container crane utilization and loading and unloading productivity to effective time of container vessel.